Morphometry and morphology of the antennae of Panstrongylus megistus Burmeister, Rhodnius neglectus Lent, Rhodnius prolixus Stal and Triatoma vitticeps Stal (Hemiptera: Reduviidae) - Rosa, João Aristeu da [UNESP]; Freitas, Silvia C M de [UNESP]; Malara, Flávio F [UNESP]; Rocha, Cláudia S [UNESP] (Sociedade Entomológica do Brasil, 2010)
The length of the four right antennal segments from nymphs and adults of Panstrongylus megistus Burmeister, Rhodnius neglectus Lent, Rhodnius prolixus Stal and Triatoma vitticeps Stal were measured. The length of the antennal segments of the adults of all four species, 4th and 5th instars of P. megistus, and 5th instar of R. neglectus and R. prolixus followed the same pattern: 2nd>3rd>4th>1st. The pattern of 1st and 2nd instars of P. megistus was: 4th>3rd>2nd>1st. For 3rd instars of P. megistus, 1st and 2nd instars of R. neglectus and R. prolixus they were: 3rd>4th>2nd>1st. Third and 4th instars of Rhodnius neglectus and R. prolixus had a pattern of: 3rd>2nd>4th>1st. Only T. vitticeps showed the same pattern (4th>3rd>2nd>1st) for all five instars. The morphological study of the second antennal segment by scanning electron microscopy (SEM) disclosed that the first instars of all four species exhibit type I bristles sensillae and one trichobothrium. Another type III bristle and basiconic, campaniform, coeloconic, trichoid sensillae and type I bristle and trichobothria were noted on their fourth instars and adults. Campaniform sensillae were noted only on T. vitticeps adults. Nodules were observed in the joint between 1st and 2nd antennal segments of adults of P. megistus and T. vitticeps, but not on R. neglectus and R. prolixus.
Keywords: Triatominae; mensuration; electron microscopy; sensilla